A date with a network - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
Scientists have been emphasizing the importance of Balanites for a long time. Researchers at the Centre National de Recherches Scientifiques (CNRS) have now decided to establish a network in order to share all the available information and to...